Contribuições de D. W. Winnicott para o estudo do distúrbio Borderline e suas implicações clínicas - Salomone, Viviane Panegassi Dorta (2009)
This dissertation had the goal of presenting Winnicott s comprehension of the borderline disorder, how the defense false self in such cases is developed, and the technic for clinic handling, a valuable contribution from Winnicott to the psicoanalysis practice. Inicially, the origin of the term borderline in Psichiatry is presented as well as some contributions to the comprehension of the case from Psicoanalysis authors, emphasizingwith the innovations proposed by Winnicott s publications. For the author, the borderline disorder presents as main characteristic the false self defense, being necessary a review of general aspects of the theory of psychosis in connection with the theory of personal development to comprehend the disorder, and to clarify concepts like the environment, trauma, and unthinkable agony. It is relevant the importance that the author gives to the handling, innovative and original technique which allows for the analyst to adapt to the patient s real needs, offering the necessary holding for the patient s regression to a stage of absolute dependency, a moment in which the maturing development was interrupted because of a environmental deficiency. Finally, synthesis of borderline cases held by the author are presented, reinforcing the relevance of those patients going through the experience with the analyst, more than the use of interpretations of verbal contents during the treatment